The Performance of Management Accountability in Private Higher Education and Its Problem in the Implementation of Good University Governance - Sukrisno, Heni (International Journal of Criminology and Sociology, 2022)
This study aimed to describe the performance of management accountability in private higher education and its problem in the implementation of good university governance. The study used the qualitative phenomenology approach with a case study design using five private universities in East Java, Indonesia. The universities were selected based on the cluster and rank in Indonesia. The ranking and clusterization were used to evaluate the performance of higher education in Indonesia. The data was divided into primary data from interviews and secondary data from the descriptive analysis. The result showed that all five universities have attempted to increase their performance of management accountability using the capacity-building and good university governance, respectively. However, the primary obstacle of those universities is the capacity-building itself, especially at the individual level.